The Nature of Islamic Religious Education Research Methods - Ach. Syafiq Fahmi; Halimatus Sa’diyah; Intan Dwi Permatasari; Faiqatul Munawwarah (Penerbit Hellow Pustaka, 2025)
The nature of Islamic Religious Education (PAI) research includes an in-depth understanding of the methods and approaches used to explore various aspects of religious education. PAI research aims to identify, analyze, and provide solutions to issues related to the teaching and learning process, curriculum, and the impact of education on student character development. This study aims to explore the nature of the Islamic Religious Education research method, by using a literature review, this study is expected to be able to provide a detailed explanation by referring to several strong and accountable literatures. The results of this study indicate that the Islamic Religious Education research method is a scientific way to obtain data or information from the Qur'an, al-Hadith and the opinions of scholars and Islamic education experts as they are and not as they should be with certain goals and uses. The characteristics of scientific research include: Having a Purpose, Systematic, Empirical, Objectivity, Critical, Generalizability, and Replicability, while the types of PAI research methods are generally divided into 5 types, namely; Qualitative Method, Quantitative Method, Survey Method, Expos Facto Method, and Descriptive Method